The Important Role of Ideological and Political Work in the Development of Enterprises - Yuan, Pan (Journal of Theory and Practice of Management Science, 2023)
Society is constantly developing, the economy is constantly strengthening, and the country is constantly growing. Human resources play an indispensable role in the operation and management of enterprises, as well as in the ideological and political education of employees. In order to ensure the smooth progress of political work and normal operation of the enterprise, and to ensure the stable and sustainable development of the enterprise, the ideological and political work of employees must be taken seriously and rigorously. Facing the personality and characteristics of employees, the implementation of ideological and political work will not be simple. People's consciousness constantly changes with the development of the times and the updating of social concepts, and employees' three perspectives will also be updated and changed accordingly, which to some extent affects the implementation of ideological and political work. Various constantly changing factors make it necessary for enterprises to attach importance to and timely carry out ideological and political education activities. This article explores and discusses the important role of ideological and political education in the operation and development of enterprises.